2006
DOI: 10.1088/0031-9155/51/20/019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of conformal treatment planning: a new tool for quantitative comparison

Abstract: We develop a novel radiotherapy plan comparison index, critical organ scoring index (COSI), which is a measure of both target coverage and critical organ overdose. COSI is defined as COSI=1-(V(OAR)>tol/TC), where V(OAR)>tol is the fraction of volume of organ at risk receiving more than tolerance dose, and TC is the target coverage, VT,PI/VT, where VT,PI is the target volume receiving at a least prescription dose and VT is the total target volume. COSI approaches unity when the critical structure is completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The COSI tool was found to be objective, quick and accurate tool in choosing the best plan. Similar to our results, Menhel et al found that a non-coplanar 3D plan was superior to the IMRT plan 25 . Levin et al in their retrospective study on ten patients with maxillary sinus tumors compared treatment plans of 9-field IMRT, directionally optimized IMRT, and 3D noncoplanar planning in terms of critical organ sparing and TC 27 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The COSI tool was found to be objective, quick and accurate tool in choosing the best plan. Similar to our results, Menhel et al found that a non-coplanar 3D plan was superior to the IMRT plan 25 . Levin et al in their retrospective study on ten patients with maxillary sinus tumors compared treatment plans of 9-field IMRT, directionally optimized IMRT, and 3D noncoplanar planning in terms of critical organ sparing and TC 27 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition to that, two more indexes were calculated to account for the irradiation of all OARs regarding their tolerance. One of these indexes is the Critical Organ Scoring Index (COSI) which takes into account both the target coverage and the critical organ irradiation 25,26 . The main advantage of this index is its ability to account of the irradiation of all OARs simultaneously in one index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This index could not provide dissociable information either, and there were no considerations for the tolerance levels of individual OARs. To overcome this drawback, Menhel et al 21 proposed the critical organ scoring index to compare individual involvement of the OARs specifically at various dose levels. Wagner et al 22 proposed the conformity/gradient index (CGI), which is an average of the conformity score (CGI c ) and gradient score (CGI g ).…”
mentioning
confidence: 99%